Direct and Transcutaneous Vagus Nerve Stimulation for Treatment of Tinnitus: A Scoping Review - Yakunina, Natalia; Nam, Eui-Cheol (Frontiers in Neuroscience, 2021)
Recent animal research has shown that vagus nerve stimulation (VNS) paired with sound stimuli can induce neural plasticity in the auditory cortex in a controlled manner. VNS paired with tones excluding the tinnitus frequency eliminated physiological and behavioral characteristics of tinnitus in noise-exposed rats. Several clinical trials followed and explored the effectiveness of VNS paired with sound stimuli for alleviating tinnitus in human subjects. Transcutaneous VNS (tVNS) has received increasing attention as a non-invasive alternative approach to tinnitus treatment. Several studies have also explored tVNS alone (not paired with sound stimuli) as a potential therapy for tinnitus. In this review, we discuss existing knowledge about direct and tVNS in terms of applicability, safety, and effectiveness in diminishing tinnitus symptoms in human subjects. This review includes all existing clinical and neuroimaging studies of tVNS alone or paired with acoustic stimulation in tinnitus patients and outlines the present limitations that must be overcome to maximize the potential of (t)VNS as a therapy for tinnitus.